PERENCANAAN JARINGAN 5G NR DENGAN METODE CAPACITY PLANNING MENGGUNAKAN FREKUENSI 2.300 MHz DI AREA KOTA CIMAHI - H.D, Ni Ketut; Suganda Wijaya , Bagus (EPSILON: Journal of Electrical Engineering and Information Technology, 2024)
The City of Cimahi, one of the developing cities in West Java, requires reliable communication infrastructure to support its economic and social growth. However, Cimahi currently lacks 5G network coverage from any operator. Therefore, this study aims to plan a 5G NR network using the 2,300 MHz frequency for Cimahi. This study employs a quantitative method with a simulation approach using Atoll Planning software. The data analyzed includes Synchronization Signal Reference Signal Received Power (SS-RSRP) levels across the entire area of Cimahi. The study compares the planning results between capacity planning and coverage planning methods previously applied. The analysis involves calculating the network capacity required based on the number of users, area types, and signal quality levels. The analysis reveals significant differences in area coverage and signal quality between the two approaches. Capacity planning, which uses 67 sites, provides a coverage area of 9.591 km² with better signal quality (SS-RSRP > -90 dBm). In contrast, coverage planning with 26 sites covers a larger area of 27.641 km² but with lower signal quality (SS-RSRP < -90 dBm). This research offers valuable insights for designing an optimal 5G network for Cimahi by considering both capacity and coverage needs.